2020
DOI: 10.3389/fphys.2020.537778
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Suppression Reduces Anxiety-Related Overestimation of Time Perception

Abstract: Anxiety has been found to lengthen time perception, especially the time perception of negative stimuli. This anxiety-related time overestimation is thought to be mainly associated with massively increased arousal. Suppression, which can be achieved either deliberately or automatically, has been demonstrated to be effective in reducing arousal. Consequently, the present study explored the effectiveness of both deliberate suppression (Experiment 1) and automatic suppression (Experiment 2) in reducing the time di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 83 publications
(151 reference statements)
1
10
0
Order By: Relevance
“…Importantly, as hypothesized (Hypothesis 2), the results of mediating analysis of arousal on temporal dilation indicated that the decrease of arousal mediates the attenuation of temporal dilation in attractive faces, suggesting that the manipulation of automatic expression suppression decreases the arousal and consequently attenuates the temporal dilation of attractive faces. This finding is similar to previous investigation concerning emotional temporal dilation (Mella et al, 2011) or anxietyrelated temporal dilation (Yuan et al, 2020), providing empirical evidence that the attenuation of temporal dilation was associated with the downregulation of arousal.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Importantly, as hypothesized (Hypothesis 2), the results of mediating analysis of arousal on temporal dilation indicated that the decrease of arousal mediates the attenuation of temporal dilation in attractive faces, suggesting that the manipulation of automatic expression suppression decreases the arousal and consequently attenuates the temporal dilation of attractive faces. This finding is similar to previous investigation concerning emotional temporal dilation (Mella et al, 2011) or anxietyrelated temporal dilation (Yuan et al, 2020), providing empirical evidence that the attenuation of temporal dilation was associated with the downregulation of arousal.…”
Section: Discussionsupporting
confidence: 91%
“…In the dominant theoretical accounts, PA models assumed that the time perception is determined according to the number of pulses generated by a pacemaker and counted by an accumulator through a switch/gate (Treisman, 1963;Church, 1984;Gibbon et al, 1984). Based on PA models, the pacemaker rate is usually conceptualized as arousal (Lake et al, 2016;Zhang et al, 2017;Li and Tian, 2020;Yuan et al, 2020), with an increase in arousal equivalent to an increase in the pacemaker rate. This increase in the pacemaker rate results in a greater number of pulses during the timing of a specific event and eventually led to temporal dilation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations